The effect of colchicine on mortality outcome and duration of hospital stay in patients with COVID‐19: A meta‐analysis of randomized trials - Chia Siang Kow; Learn‐Han Lee; Dinesh Sangarran Ramachandram; Syed Shahzad Hasan; Long Chiau Ming; Hui Poh Goh (Immunity, Inflammation and Disease)
Abstract Background Overactivation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome can lead to severe illness in patients with coronavirus disease‐2019 (COVID‐19). The NLRP3 inhibitor, colchicine, therefore, appears to be promising for the treatment of COVID‐19. Aims We aimed to perform a meta‐analysis of randomized trials investigating the effect of colchicine in patients with COVID‐19. Materials & Methods We systematically searched electronic databases and clinical trial registries (up to October 17, 2021) for eligible studies. The outcomes of interest were all‐cause mortality and duration of hospital stay. Meta‐analysis with the random‐effects model was used to estimate the pooled odds ratio (OR) of mortality and 95% confidence interval (CI). The pooled standardized mean difference of duration of hospital stay with 95% CI between colchicine users and non‐colchicine users was estimated using Cohen's d index. Results The meta‐analyses revealed no significant difference in the odds of mortality (pooled OR = 0.76; 95% CI: 0.53–1.07), but a significant reduction in the duration of hospital stay with the use of colchicine (pooled standardized mean difference = −0.59; 95% CI: −1.06 to −0.13). Discussion and Conclusion The ability of colchicine to reduce the length of stay in hospitalized patients with COVID‐19 is consistent with its potential to prevent clinical deterioration via inhibition of NLRP3 inflammasome. Nevertheless, such beneficial effects of colchicine did not translate into mortality benefits in patients with COVID‐19.